Identifikation von Teilprozessen des situationsbezogenen funktionalen Denkens in der Sekundarstufe I (mathematica didactica, 2021)
This article identifies sub-processes of functional thinking for lower secondary grades in order to foster functional thinking pointedly. The article distinguishes “functions” as mathematical objects and “functional relationships” as phenomena in the world in order to identify sub-processes of functional thinking with regard to mathematizing and interpreting functional dependencies that can be directly targeted through task design. The empirical insights show which of the sub-processes occur with students of grade 9.